2021
DOI: 10.1002/eat.23654
|View full text |Cite
|
Sign up to set email alerts
|

Associations between orthorexia, disordered eating, and obsessive–compulsive symptoms: A systematic review and meta‐analysis

Abstract: Objective Orthorexia nervosa (ON) is defined as an unhealthy obsession with healthy eating, focusing on concerns regarding food quality and composition. Currently, there is still a lack of consensus about a clear definition of the construct. Specifically, it has yet to be clarified whether ON pertains to eating disorders (EDs) or obsessive–compulsive disorder (OCD) spectrum. Hence, we conducted a systematic review and meta‐analysis addressing the magnitude of the association between these groups of symptoms. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 92 publications
(88 reference statements)
7
25
0
Order By: Relevance
“…These results are in line with other studies showing that greater ON symptomatology is associated with greater disordered eating among adults from the general population [ 11 , 12 , 15 , 16 , 17 ]. It is worth pointing out that the recent systematic review and meta-analysis [ 18 ] on relationship between ON and disordered eating, and obsessive–compulsive (OCD) symptoms have demonstrated a moderate association between ON and EDs symptoms and a small association between ON and OCD symptoms. In addition, ON has been found to be more associated with EDs compared to OCD.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with other studies showing that greater ON symptomatology is associated with greater disordered eating among adults from the general population [ 11 , 12 , 15 , 16 , 17 ]. It is worth pointing out that the recent systematic review and meta-analysis [ 18 ] on relationship between ON and disordered eating, and obsessive–compulsive (OCD) symptoms have demonstrated a moderate association between ON and EDs symptoms and a small association between ON and OCD symptoms. In addition, ON has been found to be more associated with EDs compared to OCD.…”
Section: Introductionmentioning
confidence: 99%
“…ON is not currently recognized as an ED in DSM-5, since the great heterogeneity in its clinical presentations is insufficient to make a more specific diagnosis [21]. A history of EDs has shown positive correlations with ON in various studies [8,27]; accordingly, a recent systematic review and meta-analysis of 36 studies showed a significant, moderate association between ON and symptoms of EDs (pooled effect size = 0.36, 95% CI: 0.30-0.43) [28].…”
Section: On and The Spectrum Of Edsmentioning
confidence: 99%
“…Having an anxious personality, the need to have complete control, the phobia of food impurity, and a potential tendency to perfectionism are some of their shared characteristics [19,50]. A systematic review and meta-analysis published in 2021 showed a significant association between ON and OCD symptoms (pooled effect size = 0.21, 95% CI: 0.15-0.27) [28].…”
Section: Mental Health-related and Nutritional Correlates Of Onmentioning
confidence: 99%
“…Speci cally, the authors emphasize rigidity, perfectionism, and other obsessive-compulsive traits as their common features, while the only difference between is that OCD symptoms are related to healthy eating in ON. In their metaanalysis, Zagaria et al [12] have reported that ON symptoms are more associated with eating disorders compared to OCD, and therefore ON can be included in the DSM classi cation as an emerging eating disorder.…”
Section: Plain English Summarymentioning
confidence: 99%